Implementation of Integrated Marketing Communication in Enhancing the Competitiveness of the Cicil Emas Product Based on Maqashid Syariah at BSI KCP Medan AH. Nasution - Kennadem Kurnia Putri; Muhammad Syukri Albani Nasution; Tuti Anggraini (Majapahit Journal of Islamic Finance and Management, 2025)
This study examines the implementation of Integrated Marketing Communication (IMC) in enhancing the competitiveness of the Cicil Emas (Gold Installment) product at Bank Syariah Indonesia (BSI) KCP Medan AH. Nasution, based on the values of maqashid syariah. Using a qualitative case study approach, data were collected through interviews, observations, and document analysis to explore how IMC strategies support the bank’s efforts in promoting sharia-based products. The findings indicate that IMC plays a strategic role in strengthening BSI’s market position through the integration of advertising, public relations, literacy education, and digital marketing. The study also reveals that aligning IMC with maqashid syariah, particularly hifz al-maal (protection of wealth) and al-‘adl (justice), helps ensure that every marketing message reflects ethical and spiritual values. Despite challenges such as fluctuating gold prices and limited public literacy, the synergy between IMC and maqashid principles has enhanced customer trust and increased product participation. This research emphasizes that sharia-based IMC is not merely a marketing tool but a means of Islamic economic da’wah, fostering sustainable competitiveness grounded in transparency, justice, and blessings.